Pengaruh Pengalaman Auditor, Profesionalisme Auditor, Task Complexity, Time Pressure, Gender dan Etika Profesi Terhadap Auditor Materiality Judgments (DKI Jakarta, Indonesia) - Rudi Ginting (Universitas Serang Raya, 2024)
Abstract Public Accounting Firms are professional institutions that are obliged to uphold ethics and professionalism, and are capable of global competition on an international and national scale. Auditors are responsible for implementing professional standards and upholding the required provisions. In the implementation of audited financial reports, misinformation is still found and there are even frauds in financial reports, so that it raises questions about the professionalism of Public Accountants who should provide reports that are reliable, accurate and free of material misstatement. This debate has never been resolved, apart from involving large public accounting firms in the country and abroad. This research aims to examine the impact of experience, professionalism, complexity, pressure, gender and ethics on the auditor's assessment of materiality in audited financial reports. The research population is registered auditors at the Indonesian Institute of Public Accountants (IAPI) in the DKI Jakarta area. The simple random sampling method was used to select samples, distribute questionnaires to auditors who work at Public Accounting Firms (KAP) in the area. A total of 80 auditors filled out and returned the questionnaire as a sample. Data were analyzed using multiple linear regression with SPSS software, and tested the hypotheses in this research. Examination of the data shows that experience, professionalism, complexity, pressure and gender influence the consideration of materiality levels in financial reports. Meanwhile, professional ethics has no impact or influence on the consideration of the level of materiality in financial reports. Keywords: Experience, Professionalism, Task Complexity, Time Pressure, Gender, Professional Ethics, Materiality